Measurement of C1-Inhibitor function alone is sufficient for diagnosis of hereditary angioedema. Issue 11 (7th October 2021) - Kiani-Alikhan, Sorena; Walker, Elizabeth; Hickey, Alaco; Grigoriadou, Sofia; Buckland, Matt; Scott, Chris
Abstract : The World Allergy Organisiation/European Academy of Allergy and Clinical Immunology (WAO/EAACI) 2017/2018 guidelines recommend measuring complement4 levels, followed by C1-inhibitor level and function for diagnosis of hereditary angioedema (HAE). We analysed 6 months' worth of data generated in our laboratory which is a specialist regional immunology service and also provides laboratory service for the Barts Health immunology department, which is a GA2LEN/HAEi-Angioedema Centre of Excellence and Reference (ACARE) and hence, investigates a large number of patients for HAE. We found that an efficient and sensitive approach for laboratory diagnosis of HAE is to only test the C1-inhibitor function. This approach had a sensitivity of 100% and reduced the cost of laboratory investigations for HAE diagnosis by 45%.